The Republic of Trinidad and Tobago : celebrating a century of commercial oil production (First Magazine Ltd. LondonGB, 2009)
Presents the history of the petroleum industry in Trinidad and Tobago and looks at prospects for the future.
Keywords: PETROLEUM INDUSTRY